This paper concerns with the development of a decision support package for chipper allocation at the transmigration land preparation area. It is intended to be used by chip entrepreneur on determining the most economical chipper allocation and man power requirement. The package was developed by using Turbo Pascal, running well on the computers compatible with ISM PC (XT or AT) with minimum 640 Kb RAM and VGAISuper VGA monitor. Program testing showed that the program has a sufficient capability a - Irwan Ibnu Santoso; Setyo Pertiwi (Jurnal Keteknikan Pertanian, 1997)
This paper concerns with the development of a decision support package for chipper allocation at the transmigration land preparation area. It is intended to be used by chip entrepreneur on determining the most economical chipper allocation and man power requirement. The package was developed by using Turbo Pascal, running well on the computers compatible with ISM PC (XT or AT) with minimum 640 Kb RAM and VGAISuper VGA monitor. Program testing showed that the program has a sufficient capability as a management tool.